Interaction Between Buddhist Sunday School Teacher Competence versus Student Learning Motivation - Sutiyono, Sutiyono; Lestari, Widya; Sari, Dwi Ratna; Astika, Ria; Sutawan, Komang (LPPM STIAB JINARAKKHITA LAMPUNG, 2024)
Research focused on the important role of teacher competence in shaping individual understanding of learning motivation. 170 respondents used relevant instruments to collect data. Regression analysis is used to test the independent variables, personality competence, competency, social competence and professional competence against learning motivation as a dependent variable. The results of the statistical tests show that the regression model has good quality, and there are indications of other factors that also influence it. The analysis shows that the practice of personality competencies, competences, social competencies and professional empathy has a significant and positive influence on student learning motivation. Implications, teachers' competencies can be factors that support the development of understanding and practice of Buddhist teachings in the learning environment.